Ekstrak Daun Salam (Eugenia polyantha, wight.) Sebagai Pengawet Alami Daging Ayam Broiler di Pasar Wonokromo - Hidayah, Nurul; Kusuma Wardhani, Lailia Dwi; Putri Ekapaksi, Caecilia Cindy; Wibisono, Freshinta Jellia (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2021)
This study aimed to determine the effect of bay leaf extract (Eugenia Polyantha, Wight.) as a natural preservative for broiler chicken meat in the Wonokromo market. The experimental design used in this study was a completely randomized design with 4 treatments and 5 replications, namely P0 (control), P1 (bay leaf extract 5%), P2 (15% bay leaf extract) and P3 (25% bay leaf extract). Broiler chicken thighs were soaked for 30 minutes and stored at room temperature (20-25OC) for 24 hours. The organoleptic test processed descriptively and the panelists was the researchers herself. The color of the best broiler chicken meat was at P3 with a brownish yellow color, the best broiler chicken meat smell was P3 with a slightly rotten smell and a bit of bay leaf aroma and the best broiler chicken meat texture was 2, namely in P2 and P3 with a slightly soft texture. The initial test of decay (Eber test) and total bacterial colonies (TPC) used statistical analysis of analysis of variance data. The mean initial rot (Eber) was at P0 1.00, P1 0.83, P2 0.33, P3 0.17. The average total bacterial colonies (TPC) were at P0 3.35 x 106, P1 3.03 x 106, P2 2.71 x 106, P3 2.50 x 106. The results of statistical analysis showed that bay leaf extract had a significant effect on early rot (Eber) and total bacterial colonies. (TPC) of broiler chicken in the Wonokromo market results was (P<0.05), although the total number of bacterial colonies (TPC) has exceeded the maximum TPC limit according to SNI No.3924-2009 which achieved 1x106/cfu. The conclusion of this study was that the concentration of 25% bay leaf extract produced the best durability in broiler chicken meat with organoleptic results of a brownish yellow color, a slightly rotten odor and a slight aroma of bay leaf and also a slightly soft texture, the initial value of rottenness (Eber test) was 0.17 ± 0.40 and total value of bacterial colonies 2.50 x 106 ± 0.57 x 106/cfu. .